Creep in Ceramics - Pelleg, Joshua (Solid Mechanics and Its Applications, 2017)
This book focuses on Creep in Ceramics. The book consists of two parts. In part A general knowledge of creep in ceramics is considered, while part B specifies creep in technologically important ceramics, namely creep in oxide ceramics, carnides and nitrides. While covering all relevant information regarding raw materials and characterization of creep in ceramics, the book also summarizes most recent innovations and developments in this field as a result of extensive literature search.